(untitled) (Al-Academy, 2020)
Advertisements containing images of women represent one of the most controversial topics of the advertising industry and has an impact on people and trends. This study aims to determine the typical mental image of women purveyed through visual advertising in the Arab media. It also aims to find out whether these advertisements portray women positively or negatively, in addition to investigating the reasons for the recent negative portrayal of women in commercials. The study adopted a descriptive-analytical approach to achieve these objectives. The results indicate that advertising designs that carry images of women displayed in the Arab media create strong mental images. Repetition reinforces these images, and they emphasize the concept of women as sex objects. This concept of women as sex objects causes dissatisfaction as it is not a true reflection of women in society. The results also confirmed that women appear negatively in advertisements. The most important reasons the advertisements appeared to depict women negatively are an obsession with material gain and the presentation of women as having a low level of awareness and understanding.